Measurement of risk efficiency on the field o rice cultivation in Bangladesh: A data envelopment framework - Ferdushi, Kanis Fatama; Kamil, Anton Abdulbasah; Mustafa, Adli; Baten, Md Azizul (2012)
he endeavor of this paper is to investigate variability of yield under Data Envelopment Analysis.Panel data were taken for this framework from 1980-2008 in the agricultural field of Bangladesh concentrated on seasonal rice crop like as Aus, Aman, and Boro.This analysis was carried to find variability of yield for different environmental risk as like for Rainfall, Temperature and also for Humidity of seasonal rice yield. Using this yield variability which is called as a production risk, presented a method of Risk minimization under Data Envelopment Analysis. For Aman Season (wet season), allocative efficiency was 77% and Risk efficiency was also equal to allocative efficiency because technical efficiency came out 100%.The results of Boro season (dry season) indicated that, mean allocative efficiency was 82.9% and risk efficiency was 82.9 %.From this results it can be concluded that risk inefficiency is due to heavy rainfall, droughtness and disproportionate humidity.